Assessment of renal artery resistive index as a predictor of esophageal varices and its bleeding risk in post-hepatitic cirrhosis - Samy Zaki; Waleed M Mousa; Abdullah H Ahmed (Wolters Kluwer Medknow Publications, 2020)
Background Bleeding from rupture esophageal varices (EV) is a major and life-threatening complication of liver cirrhosis (LC). Early detection of EV and prediction of its bleeding risk is important. Objective To assess and evaluate the resistive index (RI) of the renal artery (RA) by Doppler in various stages of portal hypertensive manifestations of LC, and their values for detection of EV and its bleeding. Patients and methods The study included 90 patients, comprising 75 patients with confirmed diagnosis of LC, classified into the following groups: group 1 included 25 patients with EV and having history of variceal bleeding episodes, group 2 included 25 patients with EV and having no variceal bleeding episodes history, and group 3 included 25 patients without EV; in addition, 15 noncirrhotic controls were included as group 4. All patients were subjected to history taking, clinical examination, laboratory investigations, calculation of some important noninvasive indices (CHILD, FIB 4, and APRI) in cirrhotic groups, abdominal ultrasonography, renal Doppler, and upper gastrointestinal endoscopy. Results RA RI served as a predictor of the presence as well as bleeding risk of EV. LT RA RI revealed that a cutoff value of 0.70 has a sensitivity of 90% and a specificity of 76% to predict EV. Moreover, LT RA RI revealed that a cutoff value of 0.70 has a sensitivity of 92% and a specificity of 40% to predict EV bleeding. RT RA RI revealed that a cutoff value of 0.70 has a sensitivity of 80% and a specificity of 76% to predict EV. In addition, RT RA RI revealed that a cutoff value of 0.70 has a sensitivity of 88% and a specificity of 52% to predict EV bleeding. Conclusion RI of the RA may help in predictions of EV and its bleeding risk. LRA RI was more sensitive for prediction of EV bleeding.